2007
DOI: 10.1007/s00442-007-0849-1
|View full text |Cite
|
Sign up to set email alerts
|

Overdispersion of body size in Australian desert lizard communities at local scales only: no evidence for the Narcissus effect

Abstract: Both local and regional processes may contribute to community diversity and structure at local scales. Although many studies have investigated patterns of local or regional community structure, few have addressed the extent to which local community structure influences patterns within regional species pools. Here we investigate the role of body size in community assembly at local and regional scales in Ctenotus lizards from arid Australia. Ctenotus has long been noted for its exceptional species diversity in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 56 publications
2
27
0
Order By: Relevance
“…It is recognized that non-random phylogenetic structure (phylogenetic overdispersion or clustering) indeed exists in animal, plant and microbial communities [38], [39], [40] where approximately sixty percent of previous studies have found evidence for phylogenetic clustering in contemporary terrestrial and plant communities [41]. Two general types of niche-based processes can produce these patterns of non-random phylogenetic community structure – environmental filtering and strong negative or positive biotic interactions.…”
Section: Discussionmentioning
confidence: 99%
“…It is recognized that non-random phylogenetic structure (phylogenetic overdispersion or clustering) indeed exists in animal, plant and microbial communities [38], [39], [40] where approximately sixty percent of previous studies have found evidence for phylogenetic clustering in contemporary terrestrial and plant communities [41]. Two general types of niche-based processes can produce these patterns of non-random phylogenetic community structure – environmental filtering and strong negative or positive biotic interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Pianka 1986Pianka , 1996James 1994;McKenzie et al 2000b;Cowan and How 2004;Rabosky et al 2007). Few of these studies, however, have examined geographic patterns in assemblage composition and, of those that have, the study areas have been in predominantly sandy regions.…”
Section: Figurementioning
confidence: 99%
“…We then test for overdispersion of sympatric species in terms of their phylogenetic relatedness and body size, with the goal of understanding whether the few cases of co-occurrence are non-random. Body size represents an important ecological trait that may influence the ability of species to coexist [42]–[44], potentially due to its relationship with other factors, such as metabolic and reproductive rates, prey preferences, and vulnerability to predators [45]. As a final treatment of questions related to the potential role of species interactions in determining current species richness, we simulated the process of inter-island colonization to determine whether the current distribution of Crocidura could be generated with a random model of dispersal that lacks ecological forces.…”
Section: Introductionmentioning
confidence: 99%